THE EFFECT OF LACTIC PHYSICAL EFFORT EXERCISES ON THE DEVELOPMENT OF FAST STRENGTH AND CONCENTRATION OF BETA HORMONE AND LACTIC ACID ON THE ACCURACY OF THE FOREHAND STROKE OF TALENTED SQUASH PLAYERS - Mohammed Ghazi Salman (Proximus Journal Publishing, 2025)
This study aimed to investigate the effect of anaerobic lactic physical effort training on developing speed, strength, the concentration of beta-endorphin and lactic acid, and the forehand accuracy in talented squash players. The researcher utilized this specific training method to address the research problem, focusing on how such anaerobic lactic effort training impacts speed strength and the biochemical variables of lactic acid and beta-endendorphin concentration in the context of forehand accuracy. The study involved designing a training program based on this approach. The sample consisted of 14 talented squash players, from whom 2 were excluded for a pilot study, leaving 12 players. These players were divided into two groups of 6 each: a control group and an experimental group, both drawn from talented players at the Iraqi Squash Federation Center in Baghdad. These selected players participated in pre- and post-tests for both groups to assess speed, strength, and analyses that were conducted for the biochemical variables of lactic acid and beta-endorphin concentration, as well as forehand accuracy. Statistical analysis of the collected data revealed key findings, including the development of speed, strength, and a reduction in the levels of biochemical variables like lactic acid and beta-endorphin concentration, all contributing to improved forehand accuracy in the sampled players. The researcher's recommendations emphasize the importance of incorporating specific anaerobic lactic physical effort training that maintains consistent intensity, aligns with the studied biochemical variables, and simultaneously enhances speed and strength for optimal forehand accuracy. This training approach is seen as a foundational element upon which other squash training methods can be built for future studies involving different player cohorts and similar game conditions
Keywords: Speed Strength; Lactic Acid Concentration; Beta-Endorphin